Do We Share a Common University Identity? - Yonezawa, Akiyoshi (International Higher Education, 2020)
The rise of East Asian knowledge economies has driven national leaders and higher education researchers to seek identities for their own universities and higher education systems. This trend may, in the end, lead to a crisis of the identity that universities have in common, as autonomous academic bodies.